Caregiver perceptions of environment moderate relationship between neighborhood characteristics and language skills among youth living with perinatal HIV and uninfected youth exposed to HIV in New York City. Issue 1 (2nd January 2019) - Kang, Ezer; Leu, Cheng-Shiun; Snyder, Jordan; Robbins, Reuben N.; Bucek, Amelia; Mellins, Claude A.
ABSTRACT: Despite the increased recognition of how neighborhood conditions bear on cognitive and academic outcomes, no studies have examined the influences of objective and subjective neighborhood indices on specific areas of cognitive functioning among youth living with perinatal HIV (PHIV). In the United States (US), this is of particular concern as HIV has disproportionately affected African American youth living in economically disadvantaged and racially segregated communities. Thus, based on a longitudinal cohort study of psychosocial and behavioral health outcomes in 340 perinatally HIV-exposed but uninfected (PHEU) and PHIV youth residing in New York City, ages 9–16 years at enrollment, we analyzed data from baseline and multiple follow-up (FU) quantitative interviews with youth and their primary caregivers, from when they were at least 13-years-old (approximately 4–6 years post enrollment). We examined the association between baseline neighborhood indices (2000 US census data and caregiver's perception of neighborhood stressors) and youth receptive language skills (PPVT; Peabody Picture Vocabulary Test) at FU2 and FU3. Census data (percentage of families in neighborhood living below the national poverty rate, median neighborhood household income, and percentage of residents professionally employed) were not independently associated with PPVT scores at both follow-ups. However, in the logistic regression model, the more caregivers perceived their neighborhood as stressful and subjected to violence, the stronger the relationship between census data indicators of low resource neighborhoods and lower PPVT scores for both groups. Findings support "place-based" policies and practices that alleviate caregiver experiences of neighborhood stressors which may contribute to improved cognitive outcomes for youth living with and affected by PHIV.